Food loss analysis in Nigeria: A systematic literature review - Abulude, Ifeoluwa; Wahlen, Stefan; Justus Liebig University Giessen (My University, 2024)
The issue of food loss and waste is a complex one that must be addressed if sustainable food systems are to be achieved. In the Global South, as evidenced by Nigeria, two paradoxical trends can be observed. Firstly, substantial losses of arable crops occur during the production and distribution stages. Secondly, Nigeria is affected by food scarcity, which is in part a consequence of losses occurring at these stages. In terms of food availability, Nigeria ranks 26th among African countries. In light of this context and the government's expressed interest in identifying sustainable solutions to this problem, a systematic review was conducted with the objective of consolidating the fragmented studies on food loss in the region. This review provides a foundation for understanding the causes of food loss, the preventive and reduction strategies required, and for identifying promising areas for future research. The review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Checklist 2020. Following the application of inclusion and exclusion criteria, 23 studies were selected for review. A thematic synthesis was employed to integrate and examine the findings of the studies. The findings indicated that maize, rice, and cassava continued to be the most prevalent food crops in Nigeria, with cultivation occurring across the entire country. We differentiate the critical loss points for different crops, which arise between the production and distribution stages. In conclusion, this review reveals that food loss in Nigeria is a multifaceted issue requiring integrated solutions that address the natural, social, and material dimensions. Further empirical research, especially qualitative studies that focus on the perspectives and practices of food system actors, is essential for developing effective interventions and policies. This approach will help achieve sustainable development of food systems and advance global food security goals.
Keywords: ddc:630